Program Edukasi tentang Pengenalan Bahan Tumpatan Estetik dalam Kedokteran Gigi kepada Masyarakat Kelurahan kaligawe: Educational Program on Introducing Aesthetic Filling Materials in Dentistry to the Community of Kaligawe Village - Firdausy, Muhammad Dian; Wardhana, Erdianto Setya; Hadianto, Eko (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Oral health is an important part of overall health and can significantly impact daily quality of life. Data indicates that the prevalence of dental caries in Indonesia is 43.6%, though the use of fillings remains low, particularly in Central Java Province. Observations in Kaligawe Village show that many people prefer tooth extraction over fillings due to a lack of understanding of aesthetic filling materials, such as composite resin and Glass Ionomer Cement (GIC), which are more aesthetically pleasing than amalgam. This community service program aims to improve public knowledge of various types of aesthetic filling materials. Methods used include an initial survey, the creation of educational materials, a pretest, counseling sessions, a posttest, and interactive discussions. Results show a significant increase in the average posttest score (71.38) compared to the pretest score (42.07), with a p-value of <0.001. This interactive approach has proven effective in enhancing public understanding of aesthetic dental filling options, enabling them to make more informed health decisions